Infections and cancer: debate about using vaccines as a cancer control tool - Mbulaiteye, Sam M (BioMed Central, 2013)
In 2012, Infectious Agents and Cancer commissioned a thematic series collection of articles on Prevention of HPV related cancer. The articles have attracted wide interest and stimulated debate, including about the utility of vaccines in cancer control. The application of vaccines to cancer control fulfills a promise envisioned at the turn of the 20(th) century when remarkable experiments showed that some cancers were caused by infections. This suggested the possibility of applying infection-control strategies to cancer control. Vaccines represent the most practical cost-effective technology to prevent wide human suffering and death from many acute infectious diseases, such as small pox or polio. Hitherto applied to control of acute fatal infections, vaccines, if developed, might provide a potent way to control cancer. The articles in the HPV thematic series show success in developing and applying a vaccine against human papilloma virus (HPV). A vaccine is also available against hepatitis B virus (HBV), which causes liver cancer. These vaccines augment the tools available to control the associated cancers. Scientific endeavor continues for six other cancer-associated infections, mostly viruses. Not surprisingly, debate about the safety of vaccines targeting cancer has been triggered in the scientific community. Questions about safety have been raised for those populations where other means to control these cancers may be available. Although it is difficult to quantify risk from vaccines in individuals where other cancer control services exist, it is likely to be low. Vaccines are much safer today than before. Technological advancement in vaccine development and manufacture and improved regulatory review and efficient distribution have minimized substantially the risk for harm from vaccines. Formal and informal debate about the pros and cons of applying vaccines as a cancer control tools is ongoing in scientific journals and on the web. Infectious Agents and Cancer encourages evidence-based discussion to clarify understanding of the role of vaccines in cancer control. In a similar vein, the journal will not consider anecdotal reports and rhetorical arguments because they are unlikely to inform policy, regulation, or the public.